1974
DOI: 10.1111/j.1365-3180.1974.tb01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Bud inhibition of Cyperus rotundus L. tubers by inhibitor β or abscisic acid and the reversal of these effects by N‐6‐benzyl adenine*

Abstract: Summary: Résumé: Zusammenfassung The acidic ether fraction of methanol extracts from Cyperus rotundus L. (purple nutsedge) tubers contained inhibitory substances described hereafter as inhibitor β. Inhibitor β inhibited sprouting of excised C. rotundus buds and also the elongation of wheat coleoptiles. The inhibition of bud sprouting by inhibitor β was reversed by the application of N‐6‐benzyl adenine (BA). Applications of abscisic acid (ABA) also inhibited sprouting of the excised buds and this was similarly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Phenolic compounds (Friedman & Horowitz 1971; Jangaard et al 1971) and abscisic acid (Teo et al 1974) were found in tubers, and were suggested to be substances that may inhibit tuber sprouting. Teo et al (1974) also showed that the treatment of buds with abscisic acid inhibited sprouting, which was reversed by the presence of N ‐6‐benzyladenine. They suggested that a balance of inhibitors (possibly abscisic acid and other substances) and promoters (possibly cytokinins and other substances) controls dormancy in purple nutsedge tubers.…”
Section: Tuber Dormancy and Agementioning
confidence: 99%
“…Phenolic compounds (Friedman & Horowitz 1971; Jangaard et al 1971) and abscisic acid (Teo et al 1974) were found in tubers, and were suggested to be substances that may inhibit tuber sprouting. Teo et al (1974) also showed that the treatment of buds with abscisic acid inhibited sprouting, which was reversed by the presence of N ‐6‐benzyladenine. They suggested that a balance of inhibitors (possibly abscisic acid and other substances) and promoters (possibly cytokinins and other substances) controls dormancy in purple nutsedge tubers.…”
Section: Tuber Dormancy and Agementioning
confidence: 99%